Cm-level high accurate point positioning with satellite-based GNSS correction service in dynamic applications. Issue 2 (4th May 2021) - Alkan, Reha Metin
ABSTRACT: Nowadays, new alternatives have begun to offer the possibility of positioning as a combination of NRTK&PPP techniques. As one of them, Trimble CenterPoint RTX Correction Service provides cm-level accurate GNSS positioning based on the generation and delivery of corrections on the global scale through the satellite or Internet. In this study, usability of RTX correction service in kinematic applications and its attainable accuracy were investigated. In order to do this, two kinematic tests were carried out in Obruk Lake Dam, Çorum, Turkey. The results show that the RTX correction service provides cm-accurate point positioning by using a single GNSS receiver.